1892 Ala. Laws 292, ch. 140 - (:unkn) unknown (General Publisher, 1892)
Approved the town of Demopolis to require licensing but also placed a maximum license fee of one hundred dollars on dealers of pistols, pistol cartridges, bowie knives, dirk knives.Gun shops, or gun repair shops capped at five dollars.
--
Keywords: LICENSE - DEALERS